Juridical Analysis Of Patent Disclaimer Related To Improvement Of Inventions (Case Study on Supreme Court Decision Number 802 K/PDT. Sus/2011) - Bondan Girsang (Institute Of computer Science (IOCS), 2020)
Disclaimer of Patents Related to Improvement of Inventions takes into account the provisions regulated by Law Number 14 of 2001 and Government Regulations of 1999. Based on the regulations regulated by the Patent Law, the party applying for a patent is referred to as the Applicant and is requested to the Directorate General of Patents. In the refusal decision, if the applicant has objections to the decision by the Directorate General of Patents, it can make an appeal to the Patent Appeal Commission, if it is still rejected, it can take legal action, namely a lawsuit to the Commercial Court, and an appeal to the Supreme Court. This research was conducted using normative legal writing methods or library law research. The data used were primary, secondary, and tertiary legal materials, while the data collection was carried out by library research. The method used in analyzing the data is qualitative analysis. Based on the results of the author's research, namely the decision of the Supreme Court in the case of rejection of patents related to the improvement of this invention is due to the applicant's lack of observance of the legal remedies taken, where the decision of the supreme court did not discuss, or alluded to, the object for which the patent was requested, due to the fault of the applicant. who are late in filing their lawsuit to the court, in accordance with the provisions of the Patent Law, which is 3 months after receiving the rejection decision from the Directorate General.